2016
DOI: 10.5152/tpd.2015.4318
|View full text |Cite
|
Sign up to set email alerts
|

Four Hydatid Cysts in One Family: Is Family Screening Necessary?

Abstract: ÖZKist hidatik çoğunlukla Echinococcus granulosusun neden olduğu paraziter kistik bir hastalıktır. Enfekte köpekten bulaşan parazit, hayvancılığın yaygın olduğu bölgelerde daha yaygın görülmektedir. Bulantı, kusma ve ateş yakınmaları ile başvuran 10 yaşındaki ilk olgunun muayenesinde sağ akciğerde solunum sesleri azalmış ve krepitan ralleri bulunmaktaydı. Hepatomegali saptanan hastanın, radyolojik görün-tülemelerinde akciğer ve karaciğerinde kist saptandı. Hastanın kist hidatik tanısının serolojik olarak da do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Akgün et al, [17] reported that cyst formation was detected radiologically in 100 of 163 cases studied in their research, 70% of the cases had liver, 25% lung, and 5% other organ involvement. Karadagli et al, [18] reported that it was possible to observe the disease more commonly in individuals who share the same environment and consume similar foods, considering the disease's mode of transmission. The educational backgrounds, living environments, occupations, hobbies and socioeconomic statuses of individuals in a society affect their risk of being infected by E. granulosus.…”
Section: Resultsmentioning
confidence: 99%
“…Akgün et al, [17] reported that cyst formation was detected radiologically in 100 of 163 cases studied in their research, 70% of the cases had liver, 25% lung, and 5% other organ involvement. Karadagli et al, [18] reported that it was possible to observe the disease more commonly in individuals who share the same environment and consume similar foods, considering the disease's mode of transmission. The educational backgrounds, living environments, occupations, hobbies and socioeconomic statuses of individuals in a society affect their risk of being infected by E. granulosus.…”
Section: Resultsmentioning
confidence: 99%
“…It is seen as endemic in regions such as Middle Eastern countries where animal breeding is common like eastern part of our country. There are also reports in the literature suggesting that family screening should be performed, especially when a newly diagnosed patient is identified in endemic areas [2] .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the transmission of the definitive host to humans occurs via the fecal-oral route and no reports have ever found genetic traits that predispose to the infection [ 9 ]. Nonetheless, transmission within family groups is seldom addressed in the literature, with scarce reports such as those by Musio, who documented EQ infection in seven out of 11 members of an Athenian family in Greece [ 9 ]; Karadağlı, reporting CE in four family members [ 10 ]; Yang, who observed a prevalence of 9% for CE and 5.9% for alveolar echinococcosis (a combined prevalence of 14.9%) among individuals from Nanwan, Ningxia Hui, China. This study involved an Islamic community comprising 167 members across four families, wherein 12 family members died to CE [ 11 ]; and Larrieu in a case-control study of the risk factors for CE among children in Rio Negro, Argentina, founded that the main risk factor significantly associated with CE were having a family member with the disease (OR = 3.11; CI = 0.92–10.47) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%